2018
DOI: 10.2147/jpr.s153456
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative analgesia with a buprenorphine transdermal patch for hallux valgus surgery: a prospective, randomized, controlled study

Abstract: PurposeHallux valgus surgery often results in significant postoperative pain. Adequate control of pain is essential for patient satisfaction and improves the outcome of the procedure. This study aimed to investigate the perioperative analgesic effect of a buprenorphine transdermal patch in patients who underwent hallux valgus surgery.Patients and methodsA total of 90 patients were randomly divided into the following three groups based on the perioperative analgesic method: flurbiprofen axetil intravenous injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…As for postoperative pain medications, five studies showed lower rescue analgesic dosages in transdermal buprenorphine groups compared to placebo, 18 , 19 tramadol 16 and celecoxib. 23 Four studies showed no difference in additional analgesia usage with transdermal buprenorphine compared to transdermal fentanyl, 15 tramadol, 17 , 19 celecoxib 22 and flurbiprofen. 23 Two studies compared different doses of buprenorphine, in one the rescue analgesic consumption was higher in patients receiving 10 mcg h −1 than in patients receiving 20 mcg h −1 , 18 while in the other study rescue analgesic consumption decreased and transdermal buprenorphine dosage increased from 17.5 mcg h −1 to 32 mcg h −1 and 52.5 mcg h −1 .…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…As for postoperative pain medications, five studies showed lower rescue analgesic dosages in transdermal buprenorphine groups compared to placebo, 18 , 19 tramadol 16 and celecoxib. 23 Four studies showed no difference in additional analgesia usage with transdermal buprenorphine compared to transdermal fentanyl, 15 tramadol, 17 , 19 celecoxib 22 and flurbiprofen. 23 Two studies compared different doses of buprenorphine, in one the rescue analgesic consumption was higher in patients receiving 10 mcg h −1 than in patients receiving 20 mcg h −1 , 18 while in the other study rescue analgesic consumption decreased and transdermal buprenorphine dosage increased from 17.5 mcg h −1 to 32 mcg h −1 and 52.5 mcg h −1 .…”
Section: Resultsmentioning
confidence: 98%
“…Surgical procedures included spine surgery, 17 , 19 , 22 major 15 and elective 18 abdominal surgery, hysterectomy and myomectomy, 20 , 21 hip surgery, 16 and hallux valgus 23 corrections. Transdermal buprenorphine was started 6 to 48 hours before surgery in doses ranging from 5 mcg h −1 to 52.5 mcg h −1 15 , 16 , 17 , 18 , 22 , 23 and maintained for 1–7 days after the procedure. Only one study initiated transdermal buprenorphine 36 hours after surgery and maintained it for 28 days after the procedure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations